Description of three new Sphaerolaimus species (Nematoda: Sphaerolaimidae) form the South China Sea - Zograf, Julia K.; Pavlyuk, Olga N.; Trebukhova, Yulia A.; Tu, Nguyen Dinh (Zootaxa, 2020)
The family Sphaerolaimidae Filipjev, 1918 combines nematodes characterized by finely striated cuticle, round amphids, broad buccal cavity with longitudinal ribs, and females with one anterior ovary. Sphaerolaimus Bastian, 1865 species from this family are found in intertidal and subtidal sediments and have also been reported from mangroves and estuary. Three new species of Sphaerolaimus were found and described from the South China Sea. Sphaerolaimus callisto sp. nov. is characterized by the relatively long body, small amphids and long spicules. Sphaerolaimus callisto sp. nov. is similar to S. cuneatus Paramonov, 1929, but differs by the longer body (2350–2690 µm vs 1980–1990 µm), index b (5.1–5.6 vs 3.9–4.1), absence of precolacal supplements, and longer spicules (321–356 µm vs 270 µm). Sphaerolaimus ganymede sp. nov. is characterized by large amphids and the presence of sexual dimorphism in amphid size. Sphaerolaimus ganymede sp. nov. is close to Sphaerolaimus maeoticus Filipjev, 1922, but differs by the presence of lateral alae, indexes a (12.3–17.5 vs 20–27) and c (7.9 vs 9–10), bigger amphids in male (14.6–15.7 µm vs 11 µm). Sphaerolaimus io sp. nov. is characterized by small amphids and short apophyses of gubernaculum. Sphaerolaimus io sp. nov. is similar to Sphaerolaimus pacificus Allgen, 1947, but differs by bigger size (1480–1525 µm vs 1140 µm), presence of lateral alae, and index c (7.5–8 µm vs 14.3 µm). After critical evaluation of the genus we recognize 35 valid species and provide dichotomous and pictorial keys to species.